RESOURCES OF INDUSTRY 4.0 TECHNOLOGIES FOR THE INNOVATION OF BUSINESS MODELS (Journal of Industrial and Mechanical Engineering, 2024)
: Industry 4.0 can be defined as the fusion between the production process of products or services and information and communications technologies. But the implementation of these technologies does not guarantee success and economic profitability; it requires a cultural and organizational transformation and reengineering based on the incorporation of innovation in traditional business models. This work proposes to develop the conceptual foundations that state the theoretical bases for the identification of the value creation capabilities offered by Industry 4.0 technologies and to propose an instrument for evaluating the impact of the new paradigm on the business models of Industry 4.0. local SMEs. As a result, an analysis of the applicability of the proposed conceptual framework in a technological and business context is presented in the regional industry.
Keywords: Framework; Industry 4.0; Innovation; Business Models; Technologies